ORAL PAYILLOMA AND MUCINOUS ADENOMA OF THE STOMACH IN AN ANRICAN BABOON (Papio cycnocephalus) - N. Divakaran Nair (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1996)
A case of oral papilloma and mucinous adenoma of the stomach in in African Baboon (Papio cynocephalus) is placed on record.